THE CATEGORY OF HUMAN FREEDOM AND ITS FOUNDATIONS AND GUARANTEES (a combination of legal, philosophical and religious views) - Sarvar Abdullaev Sabitovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
It is known that in fact man is naturally-physically, spiritually-morally, socially-culturally and socio-politically free. However, although man strives for unlimited freedom, his freedom is limited by various means in different periods, societies and environments, in other words, his rights and obligations are regulated by laws (sometimes contrary to the law). At this point, a number of logical questions arise: Can a regulated freedom, which is built on the basis of dependence on someone or something, be literally freedom? What should the limit of freedom be based on? Is freedom a right or an obligation or a value? In the context of these questions, the focus of our research is to study the views of philosophers and thinkers, to consider the issues of human freedom in the Islamic doctrine, which is believed by nearly 20% of the world's population. The question of freedom has been given many definitions by scholars. Among them, a relatively generalized definition is as follows: Freedom is the state of the subject, in which he is the determining cause of his actions, that is, they are not directly conditioned by other factors, including natural, social, interpersonal-communicative and individual-generic [1:355].